Investigación y Educación en Enfermería cambia para cuidar el medio ambiente - Rodríguez-Gázquez, María de los Ángeles (Investigación y Educación en Enfermería, 2016)
During the 19th century, Florence Nightingale was already promoting the study and control of the environmental causes of disease, and stated that a healthy setting was necessary to apply adequate Nursing care. Given that they are the most numerous group among healthcare professionals, nurses are present in the comprehensive care of individuals, communities, and the environment; and their role is vitally important in supporting initiatives that promote environmental responsibility and reduced impact of climate change. How to cite this article: Rodríguez-Gázquez MA. Investigación y Educación en Enfermería Changes to care for the environment. Invest Educ Enferm. 2016; 34(1): 7.